Azithromycin Susceptibility Among Neisseria gonorrhoeae Isolates and Seasonal Macrolide Use. (15th September 2018) - Olesen, Scott W; Torrone, Elizabeth A; Papp, John R; Kirkcaldy, Robert D; Lipsitch, Marc; Grad, Yonatan H
Abstract : Rising azithromycin nonsusceptibility among Neisseria gonorrhoeae isolates threatens current treatment recommendations, but the cause of this rise is not well understood. Comparing seasonal patterns in macrolide use and azithromycin resistance, we found that population-wide macrolide use is associated with increased nonsusceptibility. Abstract: Rising azithromycin nonsusceptibility among Neisseria gonorrhoeae isolates threatens current treatment recommendations, but the cause of this rise is not well understood. We performed an ecological study of seasonal patterns in macrolide use and azithromycin resistance in N. gonorrhoeae, finding that population-wide macrolide use is associated with increased azithromycin nonsusceptibility. These results, indicative of bystander selection, have implications for antibiotic prescribing guidelines.